Injection Moulding Design, Simulation and Analysis Using SolidWorks and MoldFlow - Muhamad, Azeim; Hashim, Mohd Yussni (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study analyzes and optimizes two injection molding runner designs using SolidWorks and Moldflow simulation software. It compares key metrics like fill time, pressure distribution, material flow, and defects such as sink marks and warping. The results show that a simpler, shorter runner design, Design 1, outperforms a more complex, longer design, Design 2. Design 1 achieved a shorter fill time of 1.362 seconds compared to 1.407 seconds for Design 2, and a lower pressure drop of 113.6 MPa compared to 147.0 MPa for Design 2. Additionally, it showed better material flow and fewer defects. The study highlights the importance of using design and simulation tools to optimize injection molding, offering valuable insights for industries like automotive, electronics, and medical devices.